Spatially resolved Eu(iii) environments by chemical microscopy. Issue 22 (27th September 2021) - Vogel, Manja; Steudtner, Robin; Fankhänel, Tobias; Raff, Johannes; Drobot, Björn
Abstract : Chemical microscopy provides spatial discrimination of individual europium(iii ) species – proteinaceous europium(iii ) complexes (orange) and an extracellular europium(iii )-eDNA complex (purple) – in the Shewanella -calcite-europium(iii ) system. Abstract : Chemical microscopy combines high-resolution emission spectra with Abbe-limited spatial resolution and is used for studies of inhomogeneous samples at the (sub-)micronscale. The spatial distinction of multiple Eu(iii ) coordination sites allows for a comprehensive understanding of environmental samples and highlights the applicability of Eu(iii ) as a molecular probe in medicine and biology.